TRAUMATIC THORACIC AORTIC INJURY – A CASE SERIES: English - Garcia, Rita Carreira (2021)
Introduction: Traumatic Thoracic Aortic Injury (TTAI) is a major cause of mortality in high-velocity trauma. While most cases result in instant death, TTAI may be present in patients with multiple traumatic injuries and therefore a high index of suspicion is necessary. Endovascular treatment offers significant advantages in this context and is now standard of care. The purpose of this study is to review our contemporary institutional experience with endovascular repair of TTAI. Methods: A retrospective analysis of discharge data for patients admitted with TTAI between 2010 and 2019 was performed from our institutional administrative database (level 1 trauma center). We extracted ICD-9 procedure code 39.73 — endovascular implantation of graft in the thoracic aorta and cross-checked with hospital registries to identify all TTAI cases. Follow-up was extracted from patient charts. The primary endpoints were primary technical and clinical success. Secondary endpoints were time to diagnosis and to surgical procedure relative to traumatic event, overall mortality, ongoing primary clinical success, and procedural details (upper limb revascularization, spinal drainage, systemic heparinization and endograft oversizing). Results: We identified six patients with TTAI who underwent TEVAR between 2010 and 2019. All were victims of high impact deceleration trauma, aged between 24 and 57 years old, and otherwise healthy. Additional major injuries were present in all patients (Injury Severity Score 14–57). All patients were submitted to CTA at admission which allowed for early diagnosis of TTAI and treatment in less than 24 hours in all cases expect one (which was treated in the first 48 hours). Grade III lesions were present in all six patients. All patients underwent TEVAR with 100% technical and clinical success. Three patients had a lesion that extended above the subclavian artery and consequently required subclavian coverage, but no patient was submitted to upper limb revascularization. Spinal drainage was not used in any case and there were no neurologic events. Half the patients were submitted to the procedure under systemic heparinization. The median oversizing of the endograft was 16% (10–35%). There was no in-hospital mortality nor mortality during follow-up (median duration of 35,5 months with an IIQ of 84,5 months) and the ongoing primary clinical success is 100%. Conclusion: Endovascular repair is a safe and effective therapy for TTAI even in patients with multiple trauma, and good mid-term results are expected. The procedure specifications such as the need for upper limb revascularization, use of spinal drainage, endograft oversizing, and systemic heparinization are still unclear. The long-term consequences need to be clarified.